2011
DOI: 10.1002/sia.3836
|View full text |Cite
|
Sign up to set email alerts
|

XPS determination of uranium oxidation states

Abstract: This contribution is both a review of different aspects of X-ray photoelectron spectroscopy that can help one determine U oxidation states and a personal perspective on how to effectively model the X-ray photoelectron spectroscopy of complicated mixed-valence U phases. After a discussion of the valence band, the focus lingers on the U4f region, where the use of binding energies, satellite structures, and peak shapes is discussed in some detail. Binding energies were shown to be very dependent on composition/st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(130 citation statements)
references
References 62 publications
(161 reference statements)
9
119
1
1
Order By: Relevance
“…Previous studies have revealed that the binding energy of U 4f 7/2 in UO 2 is 379.5-379.8 eV. [12][13][14][15] In addition, the separated binding energies for U(IV)-U(V) and U(V)-U(VI) states are 0.6 and 0.9 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that the binding energy of U 4f 7/2 in UO 2 is 379.5-379.8 eV. [12][13][14][15] In addition, the separated binding energies for U(IV)-U(V) and U(V)-U(VI) states are 0.6 and 0.9 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy (BE) of the U(VI) 4f 7/2 peak shifted from 381.6 eV to a higher value of 382.7 eV, greater than previously reported values for U(VI) solids. 36 The U(VI) species produced by noncrystalline U(IV) oxidation may not represent the known crystalline U(VI) phases but rather labile U(VI)-carbonate complexes, which would explain the fast release of soluble U in the presence of 10.8 mM DIC. Surprisingly, the U(VI) species quickly diminished, dropping to merely ∼24% by 13 τ when the dissolved U concentration reached its peak value (Figure 1a).…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…17,50,55,56,59,60,61,62 A special attention was paid to the study of mechanisms of structure formation, which leads to widening of main peaks and appearance of extra structure in the spectra. 50,59,63 The XPS spectra of some oxides exhibit typical shake-up satellites of about ~25% intensity of the basic peaks 41,51,60,64 The calculated spectroscopic factors f Anf reflecting the fractions of the basic peak XPS intensities with the deduction of shake-up satellite intensities for the U 4f and U 5f peaks are: f U4f =0.83 and f U5f =0.86. 65,66 Shake-up satellites are located from the basic peaks toward the higher BE by ∆E sat (U4f): ~7 eV (U 4+ ); ~8 eV (U 5+ ); ~4 eV and ~10 eV (U 6+ ).…”
Section: Introductionmentioning
confidence: 99%
“…65,66 Shake-up satellites are located from the basic peaks toward the higher BE by ∆E sat (U4f): ~7 eV (U 4+ ); ~8 eV (U 5+ ); ~4 eV and ~10 eV (U 6+ ). 60 Since the U 4f BE on the moving from UO 2 to UO 3 changes by ∆E b~2 eV, one can reliably determine uranium oxidation states for individual uranium oxides on the basis of the U 4f 7/2 BE and positions (∆E sat ) and relative intensities I sat (%) of the shake-up satellites. 56,60 The U 4f XPS structure is best resolved for the crystalline oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation